1) 4x-3x=8+13
x=21
2) 7x-6x=15+24
x=39
3) 16x +8+1=3(4x-3)
16x+9=12x-9
16x-12x= -9-9
4x=-19
x= -9/2
x = -4(1/2), x= -4,5
4) 2,4- 0,9x=3,2-0,8x+5,6
2,4-0,9x=8,8-0,8x
-0,9x+0,8x=8,8-2,4
-0,1x=6,4
x=-64
5) 27x-18-6=20x-5+2
27x-24=20x-3
27x-20x= -3+24
7x=21
x=3
8) 9(10-x) =2 (x+12)
90-9x=2x+24
-9x-2x=24-90
-11x= -66
x=6
10) (-1+247x)-7
-1+247x-7
-8+247x
11) -0,25x=5
x=-20
12) 22-x=3
-x=3-22
-x= -19
x=19
Пошаговое объяснение:
Применим формулу косинуса двойного аргумента и приведём уравнение к стандартному виду: cos2x = 2cos²x - 1
cos³x - 3cosx - ( 2cos²x - 1 ) + 3 = 0cos³x - 3cosx - 2cos²x + 1 + 3 = 0cos³x - 2cos²x - 3cosx + 4 = 0Пусть cosx = a , |a| ≤ 1 , тогда а³ - 2а² - 3а + 4 = 0а³ - а² - а² + а - 4а + 4 = 0(а³ - а²) - (а² - а) - (4а - 4) = 0а²( а - 1 ) - а( а - 1 ) - 4( а - 1 ) = 0( а - 1 )( а² - а - 4 ) = 01) а - 1 = 0 ⇔ а = 1 ⇔ соsx = 1 ⇔ x = 2пn, n ∈ Z2) a² - a - 4 = 0 D = (-1)² - 4•(-4) = 1 + 16 = 17a₁ = ( 1 - √17 )/2 ≈ - 1,5 ⇒ ∅a₂ = ( 1 + √17 )/2 ≈ 2,5 ⇒ ∅ОТВЕТ: 2пn, n ∈ Z
1
4х-13=8+3х
4х-3х=8+13
х=21